Evaluation of some pesticides of plant origin for control of anthracnose disease (Colletotrichum destructivum O’Gara) in cowpea (Asian Journal of Agriculture, 2020)
Abstract. Enyiukwu DN, Amadioha AC, Ononuju CC. 2021. Evaluation of some pesticides of plant origin for control of anthracnose disease (Colletotrichum destructivum O’Gara) in cowpea. Asian J Agric 5: 4-11. Anthracnose is a common disease of cowpea in many bean growing areas of the world. This study evaluated the effects of Alchornea cordifolia, Tabernaemontana pachysiphon, and Lantana camara as low-input biopesticides for control of the disease. The experiment was laid out in randomized complete block design (RCBD) made up of 14 treatments with 4 replications. The results indicated that all the plant materials irrespective of carrier solvent and concentrations of application significantly (P?0.05) minimized the incidence and severity of the disease, as well as improved the yield and yield parameters of the treated crop than the control. Amongst all evaluated dosages of the plant materials, 50-100 % concentration of L. camara gave the best disease control and yield improvement of the crop, followed by full strength of T. pachysiphon and A. cordifolia was the least. However, comparative to benomyl a standard fungicide, the plant-derived pesticides demonstrated lower fungitoxicity against the pathogen apart from 50-100 % extracts of L. camara which were statistically (P?0.05) at par with the effects of the fungicide. Therefore, all the plant extracts could be used at higher doses as prophylactics to stem the disease; however, L. camara could be applied at lower doses to achieve the same level of control. These plant materials overall could therefore contribute as effective bio-fungicides towards improving productivity of cowpea in the humid tropics.
Keywords: Anthracnose, bio-pesticides, cowpea, fungitoxicity, plant disease, plant extracts